Marine Group II Archaea, potentially important players in the global ocean carbon cycle - Zhang, Chuanlun L.; Xie, Wei; Martin-Cuadrado, Ana-Belen; Rodriguez-Valera, Francisco (Frontiers in Microbiology, 2015)
Marine Group (MG) I (currently known as Thaumarchaeota) and MG II Archaea were first reported over two decades ago. While significant progress has been made on MG I microbiology and ecology, the progress on MG II has been noticeably slower. The common understanding is that while MG I mainly function as chemolithoautotrophs and occur predominantly in the deep ocean, MG II reside mostly in the photic zone and live heterotrophically. Studies to date have shown that MG II are abundant in the marine aquatic environment and display great seasonal and spatial variation and phylogenetic diversity. They also show unique patterns of organic carbon degradation and their energy requirements may be augmented by light in the photic zone. However, no pure culture of MG II has been obtained and thus their precise ecological role remains elusive.